Numerical investigation of the performance of interior permanent magnet synchronous motor drive / Shahida Pervin - Shahida, Pervin (2014)
The interior permanent magnet synchronous motor (IPMSM) is getting popular in industrial drives because of its' advantageous features such as high power to weight ratio, high efficiency, high power factor, low noise, and robustness. The vector control technique is widely used for high performance IPMSM drive as the motor torque and flux can be controlled separately. Fast and accurate response, quick recovery of speed from any disturbances and insensitivity to parameter variations are some of the important characteristics of high performance drive system used in electric vehicles, robotics, rolling mills, traction and spindle drives. Despite many advantageous features of IPMSM, precise control of this motor at high-speed conditions especially, above the rated speed remains an engineering challenge. At high speeds the voltage, current and power capabilities of the motor exceed the rated limits. Consequently, the nonlinearity due to magnetic saturation of the rotor core and hence the variation of d- and q- axes flux linkages will be significant. Thus, it severely affects the performance of the drive at high speeds. The IPMSM drive can be operated above the rated speed using the field-weakening (FW) technique. In IPMSM the flux/field can only be weakened by the demagnetizing effect of d-axis armature reaction current, id. Recently, researchers developed FW control algorithms but often ignored the high precision computation of the algorithm. Mostly they simplify the equations of flux control by ignoring the stator resistance and depend on MATLAB/Simulink library. This results in improper flux weakening operation of IPMSM. However, the proper flux computation is a crucial issue for motor control particularly, at high speed condition. Therefore, there is a need to investigate the other computational methods. In this study, accurate flux estimation for proper FW operation of IPMSM is developed by incorporating the stator resistance of the motor. The Newton-Raphson method (NRM) based numerical computation is used for high precision computation of flux component of stator current, id to enhance the performance of the IPMSM drive over wide speed range. The performance of the proposed NRM based computation of id for IPMSM drive is evaluated in simulation using MATLAB/Simulink at different operating conditions. The performance of the IPMSM drive with the proposed NRM method is also compared with the conventional simplified computation of id. It has been found that the IPMSM drive with proposed calculation of id provides better response as compared to the conventional calculation of id. Thus, the proposed method could be a potential candidate for real-time field weakening operation of IPM motor. In the next step, fourth order Runge-Kutta method (RKM) is used to solve the motor differential equations and the performance of the IPMSM drive is tested and compared with the MATLAB/Simulink library built-in motor model. The results found that there is no significant difference between RKM based calculation and MATLAB/Simulink library. Thus, the MATLAB/Simulink library motor model can be used for motor drives simulation with sufficient accuracy.